An analysis of servo motor's torque calculation under the application of Maxwell stress tensr in the finite element method - Sediono, Wahju (Badan Pengkaji dan Penerapan Teknlogi, 1999)
A method of Maxwell: stress tensor for a high precision torque calculation is presented. This method is, however, not applicable for complicated geometrics found in real systems. Therefore an approach solution based on the Finite Element Method (FEM) was developed. For this purpose two variants of Maxwell calculation method were implemented and examined. The results were then compared with each other and to other method based on force displacement.